IDENTIFICATION OF IMAGE AREA CONCEPT OF TSUNAMI DISASTER RESPONSE IN COASTAL SPATIAL Case Study : Serangan Island, Denpasar, Bali - Darmawan, I Gede Surya (Universitas Pendidikan Indonesia, 2020)
Serangan Island is one of the favourite tourist destinations in Bali which is the result of reclamation in 1995-1998, famous for its image as